An Investigation Into Pyramid Company Structures And The Obstacles To The Improvement Of Corporate Governance In Malaysia & Singapore - Lim, Edwin Kuok Sim (2004)
Corporate governance is not a new development in recent times but has in view of recent financial calamities that have hit various countries, become somewhat of a hot topic of discussion. As corporate governance deals primarily with relationships between key participants in a company, this dissertation seeks to examine the role of corporate governance and its suitability in addressing a phenomenon common and endemic to some Asian companies in Malaysia and Singapore, namely that of pyramid structures employed by family or related party controlled companies. In order to set the stage for such a discussion, the paper will begin by discussing topics pertaining to the recent Asian financial crisis, corporate governance and Asia before engaging in a discussion on the differences in corporate governance in the Asian countries of Malaysia and Singapore. Following suit is an examination of corporate governance indicators and pyramid structures with the former discussing in some detail, the indicators. The latter sections deal with an explanation into pyramid structures, how it functions and how ultimate control is determined and indirectly achieved.The question, which will be addressed towards the end of this paper, is whether pyramid structures really do thwart good corporate governance. Based on available information, it is deduced based on a review of selected studies published that corporate governance and pyramid structures cannot co-exist in harmony due to the fact that whilst good corporate governance is built on principles of disclosure and regulations, pyramid company structures offend these very principles due to its practices of non-disclosure, subjectivity and lack of regulations as observed from the South East Asian corporate scene and history. Hence, it is recommended that pyramid structures be deconstructed to pave the way for good corporate governance to prevail. Towards the end of this paper are helpful suggestions and practices, which can be considered in discouraging pyramid structures and towards enhancing good corporate governance in general.